2014
DOI: 10.1371/journal.pone.0096597
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular Long-Chain Acyl CoAs Activate TRPV1 Channels

Abstract: TRPV1 channels are an important class of membrane proteins that play an integral role in the regulation of intracellular cations such as calcium in many different tissue types. The anionic phospholipid phosphatidylinositol 4,5-bisphosphate (PIP2) is a known positive modulator of TRPV1 channels and the negatively charged phosphate groups interact with several basic amino acid residues in the proximal C-terminal TRP domain of the TRPV1 channel. We and other groups have shown that physiological sub-micromolar lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, activation of PLC upon capsaicin application was confirmed by both fluorescence based PI(4,5)P 2 and PI(4)P measurements and by demonstrating IP 3 formation in TRPV1 expressing cells [64]. Subsequent publications confirmed that PI(4,5)P 2 dialysis through the patch pipette inhibited desensitization of TRPV1 expressed in SF9 insect cells [58], and in the HEK293 derivative tsA201 cells [135]. Finally it was shown that activation of native TRPV1 by capsaicin in DRG neurons leads to depletion of PI(4,5)P 2 and PI(4)P, and that inclusion of PI(4,5)P 2 or PI(4)P in the whole cell patch pipette inhibited desensitization (Fig.…”
Section: Dependence Of Trpv1 Activity On Phosphoinositides and Itsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, activation of PLC upon capsaicin application was confirmed by both fluorescence based PI(4,5)P 2 and PI(4)P measurements and by demonstrating IP 3 formation in TRPV1 expressing cells [64]. Subsequent publications confirmed that PI(4,5)P 2 dialysis through the patch pipette inhibited desensitization of TRPV1 expressed in SF9 insect cells [58], and in the HEK293 derivative tsA201 cells [135]. Finally it was shown that activation of native TRPV1 by capsaicin in DRG neurons leads to depletion of PI(4,5)P 2 and PI(4)P, and that inclusion of PI(4,5)P 2 or PI(4)P in the whole cell patch pipette inhibited desensitization (Fig.…”
Section: Dependence Of Trpv1 Activity On Phosphoinositides and Itsmentioning
confidence: 98%
“…Consistent with their low charge densities, PS, PG or PI only activated TRPV1 partially, and at extremely high concentrations 250–500 µM in excised patches, close to their limit of solubility after extensive sonication [65]. Other negatively charged lipids not related to phosphoinositides, such as DGS-NTA and long acyl chain CoA (LC-CoA) also activated TRPV1 in excised patches; in line with their higher charge densities, they had larger effects and required lower concentrations than PG, PS or PI [65, 135]. …”
Section: Dependence Of Trpv1 Activity On Phosphoinositides and Itsmentioning
confidence: 99%
“…Interestingly, LC-CoAs are potent activators of agonist-induced TRPV1 currents acting via a similar, but not identical, mechanism as PIP 2 by interacting with the same positively charged residues. Given the potential role of inflammation in the etiology of certain metabolic disorders such as obesity and diabetes, that display altered fatty acid metabolism and transport and where dietary consumption of saturated fatty acids is a determining factor, increased LC-CoA-mediated TRPV1 channel activation may be a contributing mechanism [141].…”
Section: Pain and Inflammatory Diseasesmentioning
confidence: 99%
“…Furthermore, some potent TRP agonists are lipids. The effect of lipids on TRP channels function has attracted the interest of the pharmaceutical industry and the academic research, as reflected by the number of research articles and reviews of this field [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%